Perbandingan Model Pembelajaran PAKEM Berbasis Game Wordwall dengan Model Pembelajaran Direct Instruction Terhadap Hasil Belajar - Ana, Andi Jusriana; Mohd Iskandar, Nurfarah Nabila; Al Afifah, Jaenab Athiah (UIN Sunan Gunung Djati Bandung, 2025)
This type of research is quasi-experimental, with the research design of The Matching Only Posttest Only Control Group Design. This study aims to determine the differences between the learning outcomes of students taught using the PAKEM learning model assisted by wordwall games and the Direct Instruction learning model of class VIII SMPN 2 Bontomarannu. The population used was all class VIII students at SMPN 2 Bontomarannu in the 2023/2024 academic year, consisting of 5 classes with a total of 138 students. By using the matching sample technique, two classes were obtained, namely class VIII C and VIII B with a total of 20 pairs of samples. The data analysis technique used in the study was descriptive and inferential statistical data analysis. The results of the descriptive analysis showed that the average learning outcomes of the experimental class were 71.75 where 60% of students achieved the minimum completeness score. while the learning outcomes in the control class were 36.75 with a percentage reaching a minimum completion value of 0%. Using the Mann-Whitney Test, the asymp. Sig. (2-tailed) <0.05 value was obtained, indicating that the hypothesis was accepted so that there was a significant difference in learning outcomes between students taught using the PAKEM learning model assisted by wordwall games and the Direct Instruction learning model.